Creep subsidence prediction algorithm considering the effect of stress history for subgrades - Huang, Jian; Lu, Xusheng; Hu, Hexiang (Frontiers in Materials, 2023)
Creep subsidence is the main component of post-construction subsidence of foundations, and its prediction is an important basis for arranging subsequent construction and judging the long-term stability of subgrades. Firstly, the power function model was modified to explain the creep strain of coarse grain and fine grain soils in a uniform manner. Secondly, two one-dimensional creep deformation formulas in normal consolidation and over-consolidated states were derived using the modified power function model. Then, two creep subsidence prediction algorithms considering stress history and without considering stress history were proposed. The parameters of the two prediction algorithms can be ascertained through on-site subsidence observation data. Finally, the two proposed algorithms were in comparison with two widely used subsidence prediction algorithms in practical engineering, based on field subsidence observation data from the subgrade of Haolebaoji-Ji'an Railway. According to the comparison results, the prediction algorithm considering stress history performs the most precisely and efficiently.